2015
DOI: 10.1530/rep-15-0102
|View full text |Cite
|
Sign up to set email alerts
|

Regulation and roles of Ca2+ stores in human sperm

Abstract: [Ca2 +]i signalling is a key regulatory mechanism in sperm function. In mammalian sperm the Ca2 +-permeable plasma membrane ion channel CatSper is central to [Ca2 +]i signalling, but there is good evidence that Ca2 + stored in intracellular organelles is also functionally important. Here we briefly review the current understanding of the diversity of Ca2 + stores and the mechanisms for the regulation of their activity. We then consider the evidence for the involvement of these stores in [Ca2 +]i signalling in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
84
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(91 citation statements)
references
References 136 publications
(184 reference statements)
4
84
1
2
Order By: Relevance
“…There is evidence of Ca 2+ store mobilization consistent with the occurrence of store-operated Ca 2+ entry in sperm (Blackmore 1999;O'Toole et al 2000;González-Martínez et al 2001;Costello et al 2009;Correia et al 2015).…”
Section: Orai and Stimsupporting
confidence: 54%
See 2 more Smart Citations
“…There is evidence of Ca 2+ store mobilization consistent with the occurrence of store-operated Ca 2+ entry in sperm (Blackmore 1999;O'Toole et al 2000;González-Martínez et al 2001;Costello et al 2009;Correia et al 2015).…”
Section: Orai and Stimsupporting
confidence: 54%
“…Interestingly, in human sperm NAADP induced Ca 2+ mobilization (Sánchez-Tusie et al 2014) and the AR (Arndt et al 2014) in the absence of extracellular Ca 2+ , a condition also observed by De Blas et al (2002) but implicating the IP3R instead of TPC. Since Arndt also observed colocalization of IP3R and TPC1 in lipid rafts, they proposed that acrosomal exocytosis may well fit the "NAADP trigger hypothesis" (Calcraft et al 2009), in which initial NAADP Ca 2+ release triggers further Ca 2+ release through IP3 or Ryanodine receptors located in adjacent Ca 2+ stores amplifying the signal (Correia et al 2015).…”
Section: Tpc Channelsmentioning
confidence: 93%
See 1 more Smart Citation
“…Under in vitro conditions, fatty acid free albumin is included in capacitating media to fulfil this function. The final ingredient, calcium, is required for a variety of cellular functions including hyperactivation (Correia et al 2015) and induction of the acrosome reaction following binding of the spermatozoon to the zona pellucida (Jin et al 2011, Yanagimachi 2011.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, ketamine caused a reduction in [Ca 2þ ] i that may explain the inhibited Ca 2þ -related sperm functions such as motility and the progesterone-induced acrosome reaction. Change in mammalian sperm [Ca 2þ ] i can be achieved by Ca 2þ flux into the cytoplasm from the extracellular fluid or by Ca 2þ release from stores within the cell [26,27]. In human sperm, Ca 2þ influx is predominantly controlled by CatSper [28], which is closely associated with human sperm functions.…”
Section: Discussionmentioning
confidence: 99%